Differentially expressed miRNAs in Luminal and Basal-like breast cancer - Ming-Juan ZHAO; Jiang-Bo LIU; Qian-Qian YUAN; Tong DENG; Qiao HUANG; Gao-Song WU; Cheng FANG (Yixue xinzhi zazhi)
Objective To analysis differences in differentially expressed microRNAs (miRNAs) between luminal and basal-like breast cancer, and to explore the relationship between the expression level and the prognosis of luminal and basal-like breast cancer.Methods The miRNAs microarray datasets GSE81000 and GSE40267 which included the luminal and basal-like breast cancer patients were downloaded from the Gene Expression Omnibus (GEO). The GEO2R analysis tool was used to screen differentially expressed miRNAs in luminal and basal-like breast cancer patients. The target genes of differentially expressed miRNAs were predicted by mirDIP database. The differential expression miRNAs verification was performed on human breast cancer cell lines MCF-7 and MDA-MB-468 using quantitative real-time PCR. Finally, the relationship between the expression levels of miR-199a-5p and miR-199b-5p and the prognosis of luminal and basal-like breast cancer was analyzed by Kaplan Meier plotter online survival analysis. Results There were a total of 35 differentially expressed miRNAs in luminal and basal-like breast cancer, of which 18 miRNAs were down-regulated and 17 miRNAs were up-regulated compared to luminal breast cancer. Target gene prediction results shows that were 4,180 potential target genes in these 35 differentially expressed miRNAs, among which 19 were the most related, and the corresponding differential miRNAs were miR-199a-5p and miR-199b-5p. Compared with luminal breast cancer, miR-199a-5p and miR-199b-5p were down regulated in basal-like breast cancer. Quantitative real-time PCR results showed that the expression levels of miR-199a-5p and miR-199b-5p in MCF-7 and MDA-MB-468 cells were consistent with the results of GEO2R analysis. The results of survival analysis showed that the low expression of miR-199a-5p and miR-199b-5p was associated with the decreased overall survival rate of patients with luminal A breast cancer. Conclusion 35 differentially expressed miRNAs in luminal and basal-like breast cancer were screened. Among them, miR-199a-5p and miR-199b-5p are related to the prognosis of breast cancer. These miRNAs are expected to become new therapeutic biomarkers.